Generalized granuloma annulare - Kar, S; Mohankar, A; Krishnan, A; Preetha, K (Health Renaissance, 2011)
A 55 year old female came to Skin OPD with extensive pruritic annular papules and plaques over both upper limbs, lower limbs, back and abdomen. Biopsy from one of the lesion confirmed histopathologiclly Granuloma annulare. This case is being presented for its extensive skin involvement without any systemic disorder. Keywords: Generalized Granuloma Annulare DOI: http://dx.doi.org/10.3126/hren.v9i3.5592 HR 2011; 9(3): 207-209